Asuhan Kebidanan Bayi Baru Lahir Fisiologi di Puskesmas Panincong - Musdalifah Musdalifah; Andini Aulia Ramadhani; Andi Nur Hiqmah; Vinny Alvionita; Herawaty Herawaty; Astuti Astuti (Lembaga Pengembangan Kinerja Dosen, 2023)
Physiological newborns are babies born with a gestational age of more than or equal to 37 weeks with a body weight of 2500 grams to 4000 grams. During the birth period, many physical and psychological changes begin to occur in the baby's body, therefore it requires careful supervision to determine how to adjust to life outside the womb. The purpose of this study was to apply midwifery physiology care to By